Longitudinal Associations Between Early Childhood Externalizing Behavior, Parenting Stress, and Child Media Use - McDaniel, Brandon T. (Cyberpsychol Behav Soc Netw, 2020)
Limited research has examined bidirectional associations between modern media (e.g., smartphone, tablet) use and behavior in early childhood. This study aimed to test the hypotheses that, over 6 months, (H1) child externalizing behavior would predict later media use, mediated by parenting stress, and (H2) media use would predict later externalizing behavior. Participants included mothers and fathers from 183 heterosexual couples with a child 1–5 years old, followed for 6 months—assessed at baseline, 1, and 6 months. Frequency of child media use was assessed at baseline and 6 months through parent report across eight items (e.g., television [TV], smartphone, tablet use). Child externalizing behavior was assessed through the Child Behavioral Checklist, and parent stress through the Parenting Stress Index. Hypotheses were tested using structural equation modeling. Mothers were 31.8 (standard deviation [SD] = 4.2), fathers 33.3 (SD = 4.9), and children 3.0 years old (SD = 1.2). Structural equation models showed good overall fit. As hypothesized, we found that (H1) greater child externalizing behavior predicted greater parenting stress (β = 0.48, p < 0.001), which predicted increases in child media use (β = 0.15, p < 0.05); however, (H2) child media use did not predict later externalizing behavior (β = 0.06, p = 0.23). In post hoc analyses, results differed slightly by specific type of media; for example, externalizing behavior was associated with later tablet and game use, whereas TV use predicted increases in externalizing behavior. Our results suggest that child behavior problems associate with later media use habits, possibly as a parent coping strategy, which should be considered when providing clinical guidance.